A new high-response self-balancing sensorless control system of induction motor for weft accumulator. (October 2019) - Lu, Wenqi; Wu, Di; Zhou, Yansuo; Lu, Kaiyuan; Wang, Dong; Wu, Hao; Yang, Liangliang
Abstract: The high-response and self-adaptive yarn delivery system used in weft accumulator is a critical component for improving the efficiency and quality of textile machinery. However, the existing drive system in the weft accumulator has problems such as slow start-up and slow speed-tracking responses, giving difficulties in achieving a high-efficient yarn delivery of the textile machinery. In this paper, a high-response self-balancing sensorless integrated control system of the induction motor for weft accumulator is proposed. Firstly, to enable the motor to start and respond adaptively and quickly to the number of yarn control loops and the speed control of the external equipment, a high-response sensorless vector control system for induction motor based on improved model reference adaptive control(MRAC) is proposed. Secondly, to achieve a high-response adaptive tracking performance of yarn input and output numbers and spool shaft speed, a self-balancing control strategy based on optical electromechanically integrated closed-loop control is proposed. For proving the effectiveness of the proposed scheme, a corresponding test platform was constructed for testing and validation. It can be observed from the results that the system designed in this paper has fast starting speed and better speed tracking performance, satisfying yarn delivery requirements at different speeds with high-response and adaptability.